Feature Story: Social Work student to receive Indspire Award - External Relations, University of Regina (External Relations, University of Regina, 2018)
A journey by social work student Tracie Léost, to raise awareness for missing and murdered Indigenous women and girls, is about to hit the national stage. Léost is one of the youth recipients of the 2018 Indspire Awards on March 23 held in Winnipeg, Manitoba. The ceremony, which also features performances from some of the biggest names in Indigenous entertainment, will be broadcast on APTN and CBC at a later date. Created in 1993, the awards have celebrated Indigenous successes and achievements. In 2016, an Indspire Award was given to Dr. Jo-Ann Episkenew, Director of the Indigenous Peoples’ Health Research Centre and professor of English at First Nations University of Canada. Dr. Episkenew passed away shortly before the awards ceremony. Staff no